Prime Numbers in Data Compression: Leveraging Mathematical Properties for Efficient Storage - Parameswaran.P (International Journal of Engineering and Management Research, 2020)
Data compression is a cornerstone of modern computing, enabling efficient storage and transmission of information. Prime numbers, revered for their unique mathematical properties, find intriguing applications in various data compression algorithms. This article delves into the role of prime numbers in data compression, elucidating their significance and demonstrating their utilization through equations. The study assess the importance of prime number in data compression.